Investigation of a Micro-Progressive Die Set and Single Crystal Silicon Micro-Dies. - Nehme, Christopher. (2017)
Abstract: As nano-scale devices become commercially viable, the demand for micro-scale electrical connectors to interface the macro and nano world is increasing. Machining based techniques to create individual components, such as micro-milling and micro-electro-discharge machining, are time consuming and expensive. Microfabrication techniques based on lithographic processes are quite productive for two dimensional structures, but are limited when high aspect ratio components are required. In this thesis, microforming is investigated as a means to efficiently produce high aspect ratio electrical connectors from copper foil. To demonstrate the capability of microforming, a die set was designed with the intent of producing a micro-scale right angle connector from 25 um thick annealed copper foil with a measured average grain size of 47 um. The connector consists of a nominally 280 um by 260 um tab extending vertically from a 780 um by 260 um base. Rather than using a series of separate compound dies to produce the connector, a more efficient five stage micro-progressive die set was fabricated to combine several punching stations with one bending station for each stroke of the stamping press. The die set was produced from aluminum plate by micro-milling with custom fabricated micro-cutting tools. A novel micro-press system with the ability to align micro-die sets within 1 um accuracy was used to investigate the capabilities of the die set. Microforming with the aluminum die set demonstrated some limitations of micro-milling as a method to fabricate a progressive die. Two issues were observed: (1) the as-machined dies did not exhibit sharp corners on the tooling edges responsible for shearing of the workpiece, and (2) holding size tolerance on micro-scale features e.g. punches and mating holes, concurrent with holding positional tolerance on neighboring features with macro-scale spacing, proved difficult. This resulted in a clearance gap between mating punches and holes that was larger than desired, but necessary in order to mutually align all five stations of the progressive die. Unequal and large clearance gaps, in concert with rounded shear edges, resulted in incomplete shearing of desired geometry as the workpiece strip moved through the progressive die. However, the micro-bending stage was capable of producing a right angle even in the presence of poorly sheared features. As an alternative to micro-milling dies from aluminum, lithographic methods combined with etching were investigated to micro-fabricate dies from single crystal silicon. Using conventional methods to mask the desired geometry, contemporary deep reactive ion etching was used to create holes (female die) or to create free standing pillars (male die) on silicon wafers. Prior to this research, male and female dies produced entirely from silicon have not been investigated for micro-punching metal foil. As such, this initial research focused on potential failure modes of the silicon dies due to axial punching force. Using the micro-press system, silicon punches were first tested for catastrophic failure in pure compression with the force measured with an in-line dynamometer and compared to potential buckling from analytical predictions. Die sets were fabricated from four inch diameter silicon wafers with two different crystalline orientations, <111> and <100>. Several aspect ratios were investigated (punch height/diameter= 1 to 5) by etching approximately 300 um of the 500 um thick silicon wafers to leave free standing punches with diameters ranging from 40 um to 200 um. Compression testing (n = 84) resulted in fracture of the silicon punches near the base of each punch and along what appeared to be the closest packed slip planes. There was no evidence of punch failure due to buckling. In addition, there was no statistically significant difference in maximum compressive stress to failure between the punches fabricated from either the <111> or <100> oriented wafers. In general, the punches failed when the engineering compressive stress approached approximately 2 GPa, well below the Johnson Buckling prediction of 5-7 GPa, depending on aspect ratio. The compressive failure load of the silicon punches investigated appears to be higher than required for micro-punching copper foils of interest. For example, circular silicon punches with a 200 um diameter and an aspect ratio of approximately one failed catastrophically in compression at a force near 70 N, which is an order of magnitude greater than the force necessary to punch 25 um thick copper. Following compressive testing of silicon punches to generate a catastrophic failure, wear testing was pursued to determine the feasibility of using silicon as a production die material. Compound silicon die sets were fabricated from 500 um thick, <100> oriented, silicon wafers by deep reactive ion etching to produce 200 um diameter punches with an aspect ratio equal to approximately one. Etching was also used to produce holes in female dies halves of various diameters to investigate the effect of die clearance on wear. Successive holes were punched in 25 um thick copper foil for die clearances (radial die clearance / material thickness) of 4%, 14%, 18% and 28%. A relationship between die wear and punch clearance could not be determined as silicon die sets were found to exhibit significant chipping after approximately 10-20 holes were produced. In several cases, chipping around the rim of the female die appears to have initiated high punching force and die misalignment, leading to incomplete removal of the hole punch-outs. The results from wear testing indicate that silicon as a die material may not be capable of withstanding mass production conditions, but it appears suitable for rapid prototyping a useful number of components for die geometry prove-out and application testing.; Thesis (M.S.)--Tufts University, 2014.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Thomas James.; Committee: William Messner, Valencia Koomson, and Robert White.; Keyword: Mechanical engineering.